A simple phenomenological account for the metal-induced crystallization of amorphous Ge and Si films - A. R. Zanatta (Scientific Reports)
Abstract When combined with certain metal species, films of amorphous Ge or Si can have their typical crystallization temperatures decreased, by a factor of three or four, down to ~ 200 °C. The phenomenon is called metal-induced crystallization (MIC) and, since its first observation in the late 1960’s, shows a great technological potential in producing (poly-)crystalline films of Ge or Si onto low-melting point substrates under reduced energy conditions. From the scientific point of view, the microscopic mechanisms behind the MIC phenomenon (still) represents a scientific challenge, where most of the proposed models are invariably influenced by the samples details giving the impression that they only apply to very specific metal−semiconductor combinations and/or circumstances. The lack of a simple−unified explanation of the MIC mechanism in amorphous Ge and Si films, allied to its technological importance, gave rise to this work. Accordingly, the paper starts by presenting some crucial aspects of the MIC phenomenon, as obtained from the investigation of amorphous Ge and Si films codeposited with some metals. In order to be inclusive, the experimental results of various metal−semiconductor bi-layered samples are also presented and discussed in detail. Based on the main aspects of these two (codeposited and bi-layered) metal−semiconductor systems, a simple phenomenological model is proposed to explain the MIC of amorphous Ge and Si films. The model relies on some basic chemical aspects (like electron distribution, orbital features, and bonding character) of the different atom species to account for the metal−semiconductor interaction and consequent amorphous-to-crystalline transformation. According to it, the metals presenting “extra−free” electrons into their outermost orbitals are the most effective in promoting an atom-bonding rearrangement and, therefore, in reducing the crystallization temperature of the amorphous Ge and Si films.